The Privilege of Voice as a Criterion for Sociolinguistic Inequalities - Weirich, Anna-Christine (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2022)
Drawing on a theoretical framework for describing sociolinguistic inequalities with the notions of scope and access, the idea of voice can be used to define the aim of language learning processes as strategies to overcome sociolinguistic inequalities and marginalization. Understood in the metaphorical use of “being able to speak” and “to be heard” as used by Dell Hymes, having a voice must be analyzed from an intersectional perspective as a privilege. Studying the example of a mobile speaker and her successive attempts to find voice in different linguistic relations, reveals that the listener and their attitude have to be included in discussions of the conditions for having voice. For the rigor of sociolinguistic arguments, voice should be reserved for use on an abstract level while drawing on other (sociolinguistic) notions in empirical analysis that can describe concrete manifestations of linguistic inequalities.